Trebonia kvetii gen. nov., sp. nov., an acidophilic actinobacterium, and proposal of the new actinobacterial family Treboniaceae fam. nov - Rapoport, Daria; Sagova-Mareckova, Marketa; Sedláček, Ivo; Provaznik, Jan; Králová, Stanislava; Pavlinic, Dinko; Benes, Vladimir; Kopecky, Jan (International journal of systematic and evolutionary microbiology, 2020)
A novel actinobacterial strain, designated 15TR583T, was isolated from a waterlogged acidic soil collected near the town of Trebon, Czech Republic, and was subjected to a polyphasic taxonomic characterization. Phylogenetic analysis based on 16S rRNA gene and whole-genome sequences revealed that the organism forms an individual line of descent related to the order Streptosporangiales, class Actinomycetia. The strain shared highest 16S rRNA gene sequence similarity, yet of only 92.8%, with Actinocorallia aurea IFO 14752T. The strain grew in white colonies of aerobic, Gram-stain-positive, unbranching substrate mycelium bearing single spores at hyphae tips. The major fatty acids (>10%) were iso-C16 : 0, C16 : 0, iso-C17 : 1ω9 and 10-methyl-C17 : 0. The fatty acid pattern differed from all patterns currently described for actinobacterial genera. The organism contained as major menaquinones MK9(H6) and MK9(H8), which differentiated it from other actinobacterial families. Polar lipids were composed of six unidentified glycolipids, an unidentified phosphoglycolipid, two unidentified phospholipids and two unidentified aminolipids. Whole-cell sugars contained galactose, xylose and arabinose as major components. The peptidoglycan type was A1γ meso-diaminopimelic acid. The genomic DNA G+C content was 69.7 mol%. The distinct phylogenetic position and unusual combination of chemotaxonomic characteristics justify the proposal of Trebonia gen. nov., with the type species Trebonia kvetii sp. nov. (type strain 15TR583T=CCM 8942T=DSM 109105T), within Treboniaceae fam. nov.
Keywords: acidophilic; glykolipidy; DNA bakterií; Diaminopimelic Acid; Phylogeny; acidic soil; techniky typizace bakterií; Actinobacteria; Sequence Analysis, DNA; zastoupení bazí; RNA ribozomální 16S; Glycolipids; vitamin K 2; Base Composition; RNA, Ribosomal, 16S; sekvenční analýza DNA; Peptidoglycan; DNA, Bacterial; mastné kyseliny; Phospholipids; fylogeneze; actinobacteria; Vitamin K 2; půdní mikrobiologie; Czech Republic; Bacterial Typing Techniques; buněčná stěna; fosfolipidy; Česká republika; peptidoglykan; Cell Wall; kyselina diaminopimelová; Fatty Acids; Soil Microbiology